Qualitative study of the acceptability and feasibility of acceptance and commitment therapy for adolescents with chronic fatigue syndrome - Roxanne Morin Parslow; Esther Crawley; Philippa Clery; Catherine Linney; Jennifer Starbuck; Amanda Laffan; Jamie Leveret (BMJ Publishing Group, 2021)
Background Paediatric chronic fatigue syndrome/myalgic encephalomyelitis (CFS/ME) is disabling and relatively common. Although evidenced-based treatments are available, at least 15% of children remain symptomatic after one year of treatment. Acceptance and commitment therapy (ACT) is an alternative therapy option; however, little is known about whether it is an acceptable treatment approach. Our aim was to find out if adolescents who remain symptomatic with CFS/ME after 12 months of treatment would find ACT acceptable, to inform a randomised controlled trial (RCT) of ACT.Methods We recruited adolescents (diagnosed with CFS/ME; not recovered after one year of treatment; aged 11-17 years), their parent/carer and healthcare professionals (HCPs) from one specialist UK paediatric CFS/ME service. We conducted semi-structured interviews to explore barriers to recovery; views on current treatments; acceptability of ACT; and feasibility of an effectiveness RCT. Thematic analysis was used to identify patterns in data.Results Twelve adolescents, eleven parents and seven HCPs were interviewed. All participants thought ACT was acceptable. Participants identified reasons why ACT might be efficacious: pragmatism, acceptance and compassion are valued in chronic illness; values-focussed treatment provides motivation and direction; psychological and physical needs are addressed; normalising difficulties is a useful life-skill. Some adolescents preferred ACT to cognitive behavioural therapy as it encouraged accepting (rather than challenging) thoughts. Most adolescents would consent to an RCT of ACT but a barrier to recruitment was reluctance to randomisation. All HCPs deemed ACT feasible to deliver. Some were concerned patients might confuse 'acceptance' with 'giving up' and called for clear explanations. All participants thought the timing of ACT should be individualised.Conclusions All adolescents with CFS/ME, parents and HCPs thought ACT was acceptable, and most adolescents were willing to try ACT. An RCT needs to solve issues around randomisation and timing of the intervention.